2018
DOI: 10.1097/ta.0000000000002027
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of the Western Pennsylvania regional Stop the Bleed initiative

Abstract: Economic/Decision study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…These findings align with those of other investigators promoting large‐scale training of lay community members (Lei et al, ; Neal et al, ). With continued development of such programs, potential exists for the “Stop the Bleed” education to become more widely known and recognized through development of a train‐the‐trainer community program.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with those of other investigators promoting large‐scale training of lay community members (Lei et al, ; Neal et al, ). With continued development of such programs, potential exists for the “Stop the Bleed” education to become more widely known and recognized through development of a train‐the‐trainer community program.…”
Section: Discussionsupporting
confidence: 91%
“…Neal et al reported the vital support of the Pennsylvania State Senate of STB and making training opportunities and bleeding kits available. 21 In our study, both LRs and MRs were able to achieve high scores on the objective assessment for the performance of bleeding control techniques. A statistically higher percentage of MRs reported that increasing hands-on practice time, case scenarios, and bleeding simulation were important to the STB course.…”
Section: Discussionmentioning
confidence: 52%
“…The largest experience to date of STB training for LRs was provided by Neal et al, in which an impressive almost 20,000 LRs received STB training during the 21-mo study period. 21 However, this descriptive study did not provide any objective evidence of the knowledge and skills performance of the participants. A study by Fridling et al provided a descriptive experience of training medical students as course participants and instructors.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations